The Guardians Trilogy: Island Of Glass - Book 3 - Roberts, Nora; Maarleveld, Saskia (Grand Haven, Michigan Brilliance Audio, 2016)
An archaeologist, Riley is no stranger to the coast of Clare, but now she finds herself on unsure footing, targeted by the dark goddess who wants more than the stars, more than the blood of the guardians. While searching through Irish history for clues that will lead them to the final star and the mysterious Island of Glass, Riley must fight her practical nature and admit her sudden attraction to Doyle is more than just a fling. For it is his strength that will sustain her and give her the power to run towards love, and save them all.
Keywords: Stars -- Fiction; Time travel -- Fiction; Soldiers -- Fiction; Women archaeologists -- Fiction; Werewolves -- Fiction; Mermaids -- Fiction; Wizards -- Fiction; Prophets -- Fiction; Shapeshifting -- Fiction; Psychic ability -- Fiction; Man-woman relationships -- Fiction; Ireland -- Fiction; Science fiction; Audiobooks; Fantasy fiction